Lucky child a daughter of Cambodia reunites with the sister she left behind - Ung, Loung (New York HarperCollins, 2005)
"When Loung Ung came to America in 1980 as a ten-year-old Cambodian refugee, she had already survived years of hunger, violence, and loss at the hands of the Khmer Rouge, a story she told in her bestseller, First They Killed My Father. Now, in Lucky Child, Ung writes of assimilation and, in alternating chapters, gives voice to a genocide survivor she left behind in rural Cambodia, her older sister Chou." "Loung was the lucky child, the sibling Eldest Brother chose to take with him to America. The youngest and the scrappiest, she was the one he believed had the best chance of making it. Just two years apart, Chou and Loung had bonded deeply over the deaths of their parents and sisters. As they stood holding hands in their dusty village while the extended family gathered to say good-bye, they never imagined that fifteen years would pass before they would be reunited again." "Ung describes what it is like to survive in a new culture while surmounting dogged memories of genocide and the deep scars of war. Not only must she learn about Disney characters and Christmas trees to fit in with her classmates, she must also come to understand life in a nation of peace: that the Fourth of July fireworks are not bombs and that she doesn't have to hide food in her bed every night to make sure she has enough to eat." "An accomplished activist and writer, Ung has now returned to Cambodia many times, and in this recreation of Chou's life, she writes the story that so easily could have been hers. Both redemptive and searing, Lucky Child highlights the harsh realities of chance and circumstance and celebrates the indomitability of the human spirit."--Jacket.
The Ung family tree -- Welcome to America -- Chou -- Minnie Mouse and gunfire -- War in peace -- "Hungry, hungry hippos" -- Amah's reunion -- Square vanilla journal -- Restless spirit -- Ghosts in costume and snow -- A child is lost -- The first American Ung -- Totally awesome U.S.A. -- A box from America -- The Killing fields in my living room -- Living their last wind -- Sex ed -- Betrothed -- Sweet sixteen -- A peasant princess -- Write what you know -- Flying solo -- A motherless mother -- No Suzy Wong -- Eldest brother returns -- Seeing monkey -- Khouy's town -- Ma's daughters.
Includes bibliographical references (pages 267-268)
Keywords: Ung, Chou; Ung, Chou -- Family; Cambodian Americans -- Biography; Refugees -- United States -- Biography; Sisters -- United States -- Biography; Sisters -- Cambodia -- Biography; Political atrocities -- Cambodia -- History -- 20th century; Cambodia -- Biography